ANALISIS KINERJA PEMASARAN MELALUI KEBERHASILAN IMPLEMENTASI SISTEM ENTERPRISE RESOURCE PLANNING (ERP) PADA UMKM DI SEMARANG - Mudiantono, Mudiantono; Anisa Sa’diyah, Melia (Diponegoro Journal of Management, 2015)
Number of Micro, Small and Medium Enterprises in Semarang has increased each year. However, an increasing that number are not able to show an increase in marketing performance. In fact, technology is always develop. Development of technology makes people want to get the fast service. This condition makes  Micro, Small and Medium Enterprises should think creatively to meet the needs of people. Use Enterprise Resource Planning (ERP) system is an effective method that is able to provide fast service to people needs. Enterprise Resource Planning (ERP) is a software that integrates all the business functions in the enterprise. This study aimed to determine the effect of implementation of Enterprise Resource Planning (ERP) system to improving marketing performance in Micro, Small and Medium Enterprises in Semarang. Results of this research proved that improved  marketing performance can be done throuhg 6 processes. But, the most influential process in developing marketing performance in Micro, Small and Medium Enterprises is by implementing Enterprise Resource Planning (ERP) system which  supported by choosing the accuracy of selection software and hardware. These things are the main factor in gaining the best result.